They left us everything [large type] : a memoir - Johnson, Plum (Thorndike Press large print biographies and memoirs., 2016)
After almost twenty years of caring for elderly parents -- first for their senile father, and then for their cantankerous ninety-three-year old mother -- author Plum Johnson and her three younger brothers have finally fallen to their middle-aged knees with conflicted feelings of grief and relief. Now they must empty and sell the beloved family home, twenty-three rooms bulging with history, antiques, and oxygen tanks. Plum thought: How tough will that be? I know how to buy garbage bags. But the task turns out to be much harder and more rewarding than she ever imagined. Items from childhood trigger difficult memories of her eccentric family growing up in the 1950s and '60s, but unearthing new facts about her parents helps her reconcile those relationships, with a more accepting perspective about who they were and what they valued. They Left Us Everything is a funny, touching memoir about the importance of preserving family history to make sense of the past, and nurturing family bonds to safeguard the future.